Information and Communication Technologies for Rural Development : Volume 2. An Evaluation of Telecenters in Indonesia - World Bank (Washington, DC, 2012)
Information and communication technologies (ICTs) are a potentially revolutionary means of empowering the poor. Realizing this potential will require investments that increase access to ICTs in remote low productivity areas and the development of innovative applications that cater to the needs of the poor and small firms. The costs of these kinds of investment have been decreasing rapidly, but still yield low short term private returns. The private sector cannot alone be expected to underwrite the costs of these developments. If Government does not support these public investments, economic disparities will rise, undermining social stability and future growth. Effective public sector action is required, to establish a regulatory and legal framework that enables the rise of a vibrant innovative competitive private telecommunications and ICT services sector, and to institute selective efficient and transparent public subsidies with high social payoff but low financial returns. This is needed most urgently precisely in developing country contexts where public institutions are often ineffective, corrupt and unaccountable. The challenge takes added significance in Indonesia, a country still recovering from severe economic and political crisis, hardest hit by the biggest natural disaster in recorded human history, undergoing major changes to a decentralized system of governance, and that has very weak public institutions. The overall objective of the report is to identify the policies, technologies, institutions and investments needed to improve the access of rural communities to information services in Indonesia. Specifically, the report would illustrate the opportunities that ICT offers policy makers and practitioners in agricultural and rural development and the policies and institutions that would be necessary to achieve social and economic progress on a sustainable basis for the benefit of rural populations with a focus on farming communities and women. For the purposes of the report, ICTs are defined as electronic communication technologies with a focus on the internet and telephony. Radio, multi-media, other communication tools are addressed only to a limited extent.